Student Attitudes Toward Physical and Health Education Learning Activities in Class XI at SMA N 1 Merauke - Hendra Jondry Hiskya; Arifin Ika Nugroho; Ronald; Damaris Marlissa (Technium Social Sciences Journal, 2023)
This study aims to determine the attitude of class XI students of SMA Negeri 1 Merauke towards physical education learning activities. This research is a descriptive research using a survey method with data collection techniques using a questionnaire. The subjects in this study were class XI students of SMA Negeri 1 Merauke, totaling 54 respondents. The Instrument Reliability Test uses the Alpha Cronbach formula and the reliability gain coefficient is 0.922. temporary test validity of the 34 test items all declared valid. The data analysis technique uses descriptive analysis which is outlined in the form of proportions which are divided into 4 categories, namely very positive, positive, moderately positive, and less positive. The results showed that the attitude of class XI students of SMA Negeri 1 Merauke towards Physical Education, Sports and Health was stated to be positive. In detail, 0 people (0%) stated that they were less positive, 3 people (5.56%) stated that they were quite positive, 32 people (59.26%) stated that they were positive, and 19 people (35.19%) stated that they were very positive.